Absorptive Materials -Based Cooling Technologies for Solar Thermal: A Review of Thermal Management Strategies and Performance Enhancements - Sajad W. Noori; Duaa Alaa Lafta; Alaa M. Lafta; Mustafa M. Mansour (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2026)
The growing need for utility-scale photovoltaic (PV) systems to advance environmental goals has heightened concerns about the costs of scaling and thermal control. Among all the technical problems linked to PV panels, increased temperatures are the key issue, causing reduced efficiency and module damage. When solar energy is not absorbed by the photocells, the PV module's surface temperature can rise much higher, especially in hot climates. This is especially problematic at air temperatures above 50 °C, as traditional natural convection is unable to efficiently cool the PV modules; hence, the Spanish solar PV harnessing system traps 30% of the energy in the PV modules compared to the original efficiency. Moreover, high surface temperature cause material degradation, resulting in earlier thermal failure, replacement, or the expense of disposing of the latter. This is why methods for enhancing thermal management within PV panels are among the most important aspects, and, combined with several technological advances, PV readily available and could potentially reduce the cost of solar energy in the near future.